Electric Control of the Giant Rashba Effect in Bulk GeTe. (16th October 2012) - Di Sante, Domenico; Barone, Paolo; Bertacco, Riccardo; Picozzi, Silvia
<x xml:space="preserve">Abstract</x> Relativistic effects, including the Rashba effect, are increasingly seen as key ingredients in spintronics. A link between Rashba physics and the field of ferroelectrics is established by predicting giant Rashba spin‐splitting in bulk GeTe (see the Figure showing the band‐structure as well as in‐plane and out‐ of‐plane spin polarization for a constant energy cut). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>